Effect of Region on Free and Bound Monoterpene and C13-N orisoprenoid Concentrations in Weisser Riesling Wines - Marais, J.; Versini, G.; van Wyk, C.J.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
Free and bound monoterpene and C 13-norisoprenoid concentrations of Weisser Riesling wines of different vintages and from different regions in South Africa, Germany and Northern Italy were compared. The concentrations of some of these compounds differed between climatic regions. For example, older Weisser Riesling wines from South Africa displayed significantly higher 1,1,6-trimethyl-1,2-dihydronaphthalene (TDN), trans-vitispirane and trans- 1,8-terpin concentrations than those from the cooler European countries. Canonical and stepwise discriminant analysis of the wine data allowed the successful classification of the wines according to origin. A comparison of meteorological data of the countries revealed that in the cooler wine regions of Germany and Northern Italy the average daily temperatures were lower, the average monthly rainfall higher and the daily sunshine hours fewer than in the warmer South African wine regions.